O brincar nas políticas públicas para a educação infantil brasileira: dos documentos oficiais à proposta pedagógica para a educação infantil do Sistema Municipal de Ensino de Bauru/SP - Freitas, Andreza Cristina Morais de (2021)
The present research aimed to investigate how the Municipal Education System of Bauru has interpreted and translated national public policies for IE, and how these influenced the conceptions and directions assumed for playing expressed in its municipal document. Through documentary analysis of the notebooks produced by the Coordination of Early Childhood Education - COEDI and by the Secretariat of Fundamental Education - SEF (BRASIL, 1994-1998), the National Curriculum Reference for Early Childhood Education - RCNEI (BRASIL, 1998) and the National Curriculum Guidelines for Early Childhood Education - DCNEI (BRASIL, 2009), and the Pedagogical Proposal for Early Childhood Education of the Municipal Education System of Bauru (PASQUALINI; TSUHAKO, 2016), sought to understand how the main socio-historical, political and theoretical milestones influenced public policies for Brazilian early childhood education, and the defended conceptions and guidelines for playing. The theoretical framework for studies on playing is supported by the Historical-Cultural Theory, and the methodological framework is inspired by the Policy Cycle Approach (BOWE; BALL; GOLD, 1992, 1994). The results presented from the contexts of influences, text production and context of practice point to distances and similarities between public policies for national and municipal early childhood education. This study is part of the research line “Assessment and public policies in early childhood education”, of the study group EDIPIC- Early Childhood Education and Small Childhood in Context, at Federal University of São Carlos/SP.